Autologous vs. implant-based breast reconstruction after skin- and nipple-sparing mastectomy—A deeper insight considering surgical and patient-reported outcomes - von Glinski, Maxi; Holler, Nikla; Kümmel, Sherko; Reinisch, Mattea; Wallner, Christoph; Wagner, Johannes Maximilian; Dadras, Mehran; Sogorski, Alexander; Lehnhardt, Marcus; Behr, Björn (Frontiers in Surgery, 2022)
had no cancer recurrence or metastases. Introduction Autologous (ABR) and implant-based breast reconstruction (IBR) represent the most common procedures after skin- and nipple-sparing mastectomy. This cross-sectional study is a comprehensive analysis of ABR and IBR considering surgical and patient-reported outcomes. Patients and Methods Eligible patients underwent breast reconstruction (ABR and IBR) after skin- and nipple-sparing mastectomy between 01/2014 and 12/2020 and had no cancer recurrence or metastases. Outcome parameters included Quality of life (QoL; EORTC QLQ30, - BR23, Breast-Q, CES-D), complication rates, aesthetic result and breast sensitivity. Results 108 patients participated in the study (IBR: n=72, age 48,9  9,9 years; ABR: n=36, age: 46,6  7,3 years). Mean follow-up was 27.1 9.3 (IBR) and 34.9  20.5 (ABR), respectively. IBR-patients suffered significantly more often from major complication (30.6% vs. 8.3%; p=0.01), while ABR-patients underwent significantly more often secondary procedures to improve the aesthetic result (55.6% vs. 29.2%, p=0.004). Unilateral reconstructions revealed superior aesthetic results in ABR (n.s.), while in bilateral reconstruction IBR tended to score higher (n.s.). Scar evaluation resulted in a better result of IBR in both categories (p<0.01). Breast sensitivity was severely impaired in both groups. The Breast-Q revealed a significantly higher ‘patient satisfaction with breast’ after ABR (p=0.033), while the other QoL-Tests and subscales showed no significant differences between the two procedures. Conclusion ABR is associated with a higher patient satisfaction despite the high probability of secondary procedures to improve the aesthetic outcome, whereas IBR-patients suffer more often from major complication. Furthermore, the laterality of reconstruction should be included in the individual decision-making process.